Effect of Sulfur Addition to Nickel Recovery of Laterite Ore - Eni Febriana; Agus Budi Prasetyo; Wahyu Mayangsari; Januar Irawan; Muhammad Ikhwanul Hakim; Tiffany Ary Prakasa; Andinnie Juniarsih; Ariyo Suharyanto; Iwan Setiawan; Rudi Subagja (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
This research studied the effect of the addition of sulfur on the reduction process of limonite nickel laterite ore with Ni content of 1.11wt% and Fe 48.7wt%. The stages of the research included the characterization of ore materials, preparation, mixing, pelleting, reduction, and magnetic separation. The reduction stage was carried out with several experimental variables, which were the time and temperature of the reduction, as well as the addition of reducing agents and sulfur additives. Products from the reduction process were separated magnetically, and the concentrate was then analyzed using XRD and AAS. The results showed that the addition of sulfur additives to a certain amount could cause the formation of FeS and Fe-silicate, which could increase the content and percentage of nickel recovery by suppressing the metallization of iron. The optimum conditions were obtained in the reduction process with a temperature of 1100°C for 60 minutes, with the addition of graphite reductant and sulfur additives each of 7% of the sample weight. Ni contents in the reduction product concentrate obtained were 1.98% with 96% gain, while Fe could be reduced to 29.2% with an extraction percentage of 76.1%.